Strategic Use of (Un)certainty Expressions - Lorson, Alexandra; Cummins, Chris; Rohde, Hannah (Frontiers in Communication, 2021)
Speakers have a number of options when introducing propositions which they take to be uncertain: for instance, they can use verbs such as `know', `believe' or `think'. Speakers have a number of options when introducing propositions which they take to be uncertain: for instance, they can use verbs such as `know', `believe' or `think'. The production of uncertainty expressions is highly context dependent. One promising approach to capturing the semantic meaning of these expressions takes them to be available only when the speaker's confidence in the proposition exceeds some threshold. However, it is unclear whether this approach deals satisfactorily with the full range of usages of uncertainty expressions. For instance, speakers may also use them to achieve social goals such as toning down the force of their assertion. In this case they pursue another communicative goal than just being cooperative: they also aim to be polite. The current study investigates the speakers' motivations in choosing between uncertainty expressions such as `believe' or the factive `know' in two controlled contexts. More specifically, we show that speakers' choice of expression is influenced by (i) how likely they estimate an event to be and (ii) strategic considerations relating to the communicative context in which they are working. Thus, speakers adjust their language as a manipulative process. We situate these results in the context of threshold semantics.